An Experimental Investigation on the Pool Boiling Heat Transfer of R-134a on Microporous Cu-MWCNT Composite Surfaces - Ajay D. Pingale; Anil S. Katarkar; Mahadev Madgule; Swapan Bhaumik; Sachin U. Belgamwar (Thermo, 2024)
Multiwalled carbon nanotubes (MWCNTs) exhibit outstanding physical properties, including high thermal conductivity, excellent mechanical strength, and low electrical resistivity, which make them suitable candidates for a variety of applications. The work presented in this paper focuses on the pool boiling performance of refrigerant R-134a on microporous Cu-MWCNT composite surface layers. A two-stage electrodeposition technique was used to fabricate Cu-MWCNT composite coatings. In order to achieve variation in the surface properties of the Cu-MWCNT composite surface layer, electrodeposition was carried out at various bath temperatures (25 °C, 30 °C, 35 °C, and 40 °C). All surfaces coated with the Cu-MWCNT composite demonstrated superior boiling performance compared to the uncoated surface. Heat transfer coefficient (HTC) values for Cu-MWCNT composite surface layers, prepared at bath temperatures of 25 °C, 30 °C, 35 °C, and 40 °C, exhibited improvements of up to 1.75, 1.88, 2.06, and 2.22, respectively, in comparison to the plain Cu surface.